Endomyocardial fibrosis associated with Schistosoma haematobium infection - Assimeng, J.; Segbefia, C.I.; Neequaye, J. (Ghana medical journal, 2014)
Endomyocardial fibrosis (EMF) is a form of restrictive cardiomyopathy common in the tropics and subtropics. The aetiology of EMF is unknown but helminth infestations such as schistosomiasis have been implicated. Two boys aged 8 and 10 years with EMF associated with Schistosoma haematobium, are described. The schistosomes in both cases may have been acquired from contact with contaminated water collected and stored in containers and subsequently used for bathing. Both patients were managed conservatively. Overall prognosis of EMF is poor and this report emphasizes the importance of public health interventions in the control of schistosomiasis.
Keywords: Cardiomyopathy; Endomyocardial fibrosis; Ghana; Public health intervention; Schistosoma haematobium